A ruthenium(ii) based photosensitizer and transferrin complexes enhance photo-physical properties, cell uptake, and photodynamic therapy safety and efficacy. Issue 4 (7th March 2016) - Kaspler, Pavel; Lazic, Savo; Forward, Sarah; Arenas, Yaxal; Mandel, Arkady; Lilge, Lothar
Abstract : Mixing the novel Ru 2+ complex TLD1433 with transferrin prior to administration generates a photosensitizing drug with reduced dark toxicity and improved photophysical properties including NIR activation. Abstract : Metal-based photosensitizers are of interest as their absorption and chemical binding properties can be modified via the use of different ligands. Ru 2+ based photosensitizers are known to be effective photodynamic therapy (PDT) agents against bacteria, whereas use for oncological indications in vivo has not been demonstrated with the same level of evidence. We present data showing that premixing the Ru 2+ -complex TLD1433 with transferrin increases the molar extinction coefficient, including longer activation wavelengths, reduces photobleaching rates, and reduces the toxicity of the complex improving overall PDT efficacy. As the transferrin receptor is upregulated in most malignancies, premixing the Ru 2+ complex with transferrin converts the active pharmaceutical ingredient TLD1433 into a drug of potentially considerable clinical utility.